Episodic Jurassic to Lower Cretaceous intraplate compression in Central Patagonia during Gondwana breakup - Navarrete Granzotto, César Rodrigo; Gianni, Guido Martin; Echaurren Gonzalez, Andres; Lince Klinger, Federico Gustavo; Folguera Telichevsky, Andres (Journal of Geodynamics)
From Lower Jurassic to Lower Cretaceous, several intraplate compression events affected discrete sectors of Central Patagonia, under a general context of crustal extension associated with Gondwana breakup. This was demonstrated by means of 2D and 3D seismic and borehole data, which show partial inversion of Lower and Middle Jurassic extensional structures of the Chubut and Ca ?nadón Asfalto basins, during the earliest stages of breakup. A comparison with surrounding areas in Patagonia, where similar Juras-sic intraplate compression was described, allowed the discrimination of three discrete pulses of subtle compression (C1: ∼188?185 Ma; C2: ∼170?163; C3: ∼157?136? Ma). Interestingly, episodic intraplate compressional events are closely followed by high ﬂux magmatic events linked to the westward expan-sion of the Karoo-Ferrar thermal anomaly, which impacted on the lithosphere of southwest Gondwana in Lower Jurassic. In addition, we determined the approximate direction of the main compressive strain (1) compatible with other Jurassic intraplate belts of South America. These observations led us to pro-pose a linkage between a thermo mechanically weakened continental crust due to LIPs activity, changes in plate motions and ridge-push forces generated by the opening of the Weddell Sea, in order to explain intraplate shortening, interrupted while Karoo LIPs magmatic invigoration took place. Fil: Navarrete Granzotto, César Rodrigo. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Gianni, Guido Martin. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Estudios Andinos "Don Pablo Groeber". Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Estudios Andinos "Don Pablo Groeber"; Argentina Fil: Echaurren Gonzalez, Andres. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación ...